Implementation of The Obligation To Hold Annual Members Meetings of Cooperatives In Gianyar Regency - Nuraiti, Ni Kadek; Amelia Sri Kusuma Dewi; Fathul Laila (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
Although the number of cooperatives continues to increase, challenges such as weak management, lack of training, and lack of professionalism of the supervisory body still hamper the development of cooperatives. In Gianyar Regency, many cooperatives do not hold RATs, resulting in violations of the Cooperative Law and Permenkop Number 19 of 2015 which requires a RAT at least once a year. Data from 2024 shows that 210 of the 877 active cooperatives in Gianyar did not hold a RAT. This study aims to identify deviations and their impacts as well as the responsibility of management for not holding a RAT. The implementation of the Annual Members Meeting (RAT) of cooperatives in Gianyar Regency is still ineffective due to weak internalization of legal norms, low awareness of management and members, and structural, technical, and cultural obstacles. This ineffectiveness shows that cooperative legal regulations are not optimal due to a lack of commitment and a strong legal culture. To overcome this, it is necessary to strengthen supervision by the Cooperative Service, technical training, development of digital systems, reformulation of educational sanctions, and increasing the internal capacity of cooperatives. With synergy between the government, cooperatives, and the community, the RAT can become a culture of democratic and accountable governance in accordance with legal and cooperative values.